CT and MR Imaging Findings in Sinonasal Schwannoma - Yu, E.; Mikulis, D.; Nag, S. (American Journal of Neuroradiology, 2006)
SUMMARY: We report a rare case of schwannoma of the sinonasal cavity, presenting with epistaxis and anosmia.